Disability Discourse in the Curriculum of Nigerian Theological Institutions: Constraints, Possibilities and Recommendations - Nihinlola, Emiola (Journal of disability & religion, 2016)
This article is an intentional inquiry into the quintessential nexus between disability and theological education. An appraisal of various worldviews on disability as well as its historical and contemporary implications was made, and did not leave out a profound Biblical position. It assesses the degree of preparedness of theological institutions in training theological educators, pastors, missionaries, missiologists and others in this category for the ministry to persons with disability. The article also examines the constraints theological institutions may encounter in implementing disability discourse in the existing theological education curriculum. It asserts certain possibilities upon which theological institutions can leverage upon, while suggesting some basic methodologies as windows of opportunities for theological institutions and educators as they both embark on the quest to squarely integrate disability discourse in the curriculum of theological institutions and education in Nigeria. The article closes by recommending that awareness seminars on "Practical Ministries to People Living with Disability" should be organized, and that the Ecumenical Disability Advocates Network (EDAN) should help to coordinate efforts to produce a basic text to teach selected introductory courses on disability.